KOMPUTERISASI PERSEDIAAN DAN PENJUALAN KAIN TENUN KHAS DAERAH PADA CENTRA TENUN TAJUNG PALEMBANG. - Bainil Yulina; ANGGERAINI OKTARIDA; Evada Dewata; Sarikadarwati Sarikadarwati; Yuliantina Aryani; Sulaiman Sulaiman (Politeknik Negeri Sriwijaya, 2020)
UMKM Centra Tenun Tajung is centre for woven fabric and jumputan craftsmen that is located in Jalan Aiptu A.Wahab No.36 Kelurahan Tuan Kentang Seberang Ulu 1 Palembang became an opportunity to improve culture and tour destination in Palembang. The problem is surfaced because in the data transaction recording for sales in Centra Tenun Tajung is still manual that makes it often to be mistaken in making the financial report. The solution that is proposed is to build a computerized application system for stocks and sales so that with the right system, the mistakes can be minimalized. An on-time accurate information will really help the company in making decision and deciding what steps to take to support the operation in order to improve the company. The approach method using few stages, such as preliminary survey to the partner’s location, followed with stocktaking the partner’s data and categorize the problems especially in information technology of stocks and sales. Computerized is designed with Netbeans which is an Integrated Development Environment (IDE) application based on Java fron Sun Microsystems that runs over swing.